If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 6t + -2 = 9t + 21 + -5t Reorder the terms: 5 + -2 + 6t = 9t + 21 + -5t Combine like terms: 5 + -2 = 3 3 + 6t = 9t + 21 + -5t Reorder the terms: 3 + 6t = 21 + 9t + -5t Combine like terms: 9t + -5t = 4t 3 + 6t = 21 + 4t Solving 3 + 6t = 21 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 3 + 6t + -4t = 21 + 4t + -4t Combine like terms: 6t + -4t = 2t 3 + 2t = 21 + 4t + -4t Combine like terms: 4t + -4t = 0 3 + 2t = 21 + 0 3 + 2t = 21 Add '-3' to each side of the equation. 3 + -3 + 2t = 21 + -3 Combine like terms: 3 + -3 = 0 0 + 2t = 21 + -3 2t = 21 + -3 Combine like terms: 21 + -3 = 18 2t = 18 Divide each side by '2'. t = 9 Simplifying t = 9
| 4y+3(15)(3)= | | 13m=19 | | 4(12-3p)=15p+60 | | -1(y)=-1(3x-6) | | .36(24)+0.06x=0.18(12+x) | | 8=2(x-5)+6x | | 2(x+4)=8x+7-6x+1 | | 9+3(-4x+7)=7(-3x+1)+9 | | 6x-43=461 | | 48/6=w | | 40-4= | | 3(x-0.5)=5(x+7/2)+4x-1 | | 1/2+7/10=13/10 | | 3+-2x=y | | 4/5y-2(y-4)=3y-15 | | r/9=7 | | y^3+2y^2=y+2 | | 87.6=8.8-0.2 | | 1(y)=1(-4x-6) | | 5d-4=4 | | x-3/3=4+x/4 | | 3(2x+5)=2(4x+5)+9 | | 5d-4= | | Y=x/3+12 | | 6x-5=-53 | | 1.1q-1.9-2.4q=-2.3q-3.4 | | x-3x+5x=1 | | 2/5+3x=-118/5 | | -1=x/7+1 | | 0.55x+0.05(18+x)=0.10(-41) | | -1(y)=-1(-4x-5) | | (3+2i)+(5-2i)=8 |